2016
DOI: 10.1039/c6cp05073e
|View full text |Cite
|
Sign up to set email alerts
|

Reduction enthalpy and charge distribution of substituted ferrites and doped ceria for thermochemical water and carbon dioxide splitting with DFT+U

Abstract: The thermal reduction step of substituted ferrites (MFe2O4 where M = Fe, Ni, Co, Gd) and doped ceria (MxCe1-xO2, where M = Ce, Zr, Hf and x = 0.25) in two-step thermochemical cycles for H2O and CO2 splitting is investigated within the DFT+U framework. This thermal reduction step is described as the oxygen vacancy formation energy (reduction enthalpy), i.e. the energy required to create an oxygen vacancy in the crystal lattice. Oxides with a lower oxygen vacancy creation energy are easier to reduce. A Bader cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The third term is calculated from the reduction enthalpy of NiFe 2 O 4 (DH redNiFe2O4 = 416 kJ/0.5 mol O 2 (Dimitrakis et al, 2016) and a simulation run of the NiFe 2 O 4 monolith kinetics (Kostoglou et al, 2014) and is negligible compared to the other terms.…”
Section: Thermal Modellingmentioning
confidence: 99%
“…The third term is calculated from the reduction enthalpy of NiFe 2 O 4 (DH redNiFe2O4 = 416 kJ/0.5 mol O 2 (Dimitrakis et al, 2016) and a simulation run of the NiFe 2 O 4 monolith kinetics (Kostoglou et al, 2014) and is negligible compared to the other terms.…”
Section: Thermal Modellingmentioning
confidence: 99%
“…The redox material selected for the development of porous ceramic structures was the NiFe 2 O 4 , which is a well-known and widely investigated composition [12,14,21,27,28]. NiFe 2 O 4 has also been investigated via computational chemistry (DFT calculations, [29]) where it was shown that it is one of the state-of-the-art formulations in the family of ferrite materials. The nickel ferrite powder was synthesized via the Selfpropagating High-temperature Synthesis (SHS) technique from a mixture of Fe, NiO and Fe 2 O 3 , according to the following reaction scheme:…”
Section: Synthesis Of Redox Materialsmentioning
confidence: 99%
“…5 Ceria is currently designated as the benchmark material to perform thermochemical cycles, given its ability to maintain its crystallographic structure over a large range of non-stoichiometry, together with its thermodynamically favorable oxidation and high oxygen storage capacity, which makes it suitable to perform thermochemical cycles with high performance stability. Numerous studies have been devoted to ceria [6][7][8][9][10][11][12][13][14] , and the addition of dopants [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] to enhance its redox performance. However, ceria redox activity depends on the reduction temperature and oxygen partial pressure applied during the high-temperature step, which is generally limited to 1500°C due to undesired oversintering and ceria sublimation.…”
Section: Introductionmentioning
confidence: 99%